2015
DOI: 10.1134/s0006297915050065
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedback of glycolysis and oxidative phosphorylation: Mechanisms of and reasons for it

Abstract: There are two main pathways of ATP biosynthesis: glycolysis and oxidative phosphorylation. As a rule, the two pathways are not fully active in a single cell. In this review, we discuss mechanisms of glycolytic inhibition of respiration (Warburg and Crabtree effects). What are the reasons for the existence of this negative feedback? It is known that maximal activation of both processes can cause generation of reactive oxygen species. Oxidative phosphorylation is more efficient from the energy point of view, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…On one hand, galactose did not suppress respi ration of gpm1 cells. On the other hand, we showed earli er that galactose inhibits growth of gpm1 strain on solid medium [1]. We confirmed that this result was not an arti fact of the growth on solid substrates.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…On one hand, galactose did not suppress respi ration of gpm1 cells. On the other hand, we showed earli er that galactose inhibits growth of gpm1 strain on solid medium [1]. We confirmed that this result was not an arti fact of the growth on solid substrates.…”
Section: Resultssupporting
confidence: 80%
“…Eukaryotic cells tend to avoid simultaneous activa tion of glycolysis and oxidative phosphorylation (see [1] for review). The bioenergetics of actively proliferating cells is usually based on glycolysis and not on respiration [2 4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ATP production of the cells varies with environment changes of the cells [ 25 ]. ATP in the cells is produced mainly by the glycolysis and OXPHOS [ 26 , 27 ]. The proportion of the two varies with the environment in which the cells live.…”
Section: Discussionmentioning
confidence: 99%
“…If something similar exists in higher organisms, than tightening of cell cycle arrest by retrograde signaling under stress conditions can inhibit growth of cells with non-functional mitochondria. As cancer cells typically rely on glycolysis and inhibit mitochondrial energy functions [ 44 ], such regulation could be a mechanism that suppresses proliferation of such unwanted cells in multicellular eukaryotes.…”
Section: Discussionmentioning
confidence: 99%